2010
DOI: 10.5194/aab-53-629-2010
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of distance-dependent racing performances in German Thoroughbreds

Abstract: The objective of this study was to develop a new multivariate statistical model for genetic estimation of distance-dependent racing performances in German Thoroughbreds. Analysed performance traits were »square root of distance to first placed horse in races over sprint distances (until 1 400 m)«, »square root of distance to first placed horse in races over mile distances (from 1 401 m to 1 900 m)« and »square root of distance to first placed horse in races over long distances (over 1 900 m)«. These traits wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In addition, Entin (2007) found that intact males were statistically significantly 0.7 % faster than females at distances shorter than 1609 m and 1.4 % faster at distances longer than 1609 m. Research into horse populations has been used to examine the heritability of racing performance, and it is now recognized that many measures of racing performance (particularly race speed and ratings) are heritable (More, 1999). Numerous studies have focused on the genetic influence on racing performance and the calculation of heritability coefficients for individual performance indicators (Moritsu et al, 1994;Mota et al, 1998;Williamson and Beilharz, 1998;Sobczyńska and Lukaszewicz, 2004;Taveira et al, 2004;Svobodova et al, 2005;Bakhtiari and Kashan, 2009;Thiruvenkadan et al, 2009;Bugislaus, 2010;Tozaki et al, 2012;Bower et al, 2013;Velie et al, 2014;Bailey et al, 2022).…”
Section: The Effect Of the Race Distancementioning
confidence: 99%
“…In addition, Entin (2007) found that intact males were statistically significantly 0.7 % faster than females at distances shorter than 1609 m and 1.4 % faster at distances longer than 1609 m. Research into horse populations has been used to examine the heritability of racing performance, and it is now recognized that many measures of racing performance (particularly race speed and ratings) are heritable (More, 1999). Numerous studies have focused on the genetic influence on racing performance and the calculation of heritability coefficients for individual performance indicators (Moritsu et al, 1994;Mota et al, 1998;Williamson and Beilharz, 1998;Sobczyńska and Lukaszewicz, 2004;Taveira et al, 2004;Svobodova et al, 2005;Bakhtiari and Kashan, 2009;Thiruvenkadan et al, 2009;Bugislaus, 2010;Tozaki et al, 2012;Bower et al, 2013;Velie et al, 2014;Bailey et al, 2022).…”
Section: The Effect Of the Race Distancementioning
confidence: 99%